The Effect of Investment Knowledge on Investment Decisions Mediated by Investment Interest (A Comparative Study of UISU and UMN Students) - Hasibuan, Anisah Zuhra; Mas’ut, Mas’ut; Rangkuti, Lusi Elviani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the effect of investment knowledge on investment decisions, moderated by investment interest, among students at Universitas Islam Sumatera Utara (UISU) and Universitas Muslim Nusantara (UMN). The research examines whether investment knowledge directly influences investment decisions and how investment interest strengthens this relationship. Using statistical analysis, the t-value of 4.045 with a significance level of 0.021 was obtained, indicating that investment knowledge significantly affects investment decisions when moderated by investment interest. The findings reveal that investment knowledge positively influences investment interest, and investment interest plays a key role in strengthening the effect of knowledge on investment decisions. Specifically, UISU and UMN students with good investment knowledge tend to be more active in making investment decisions, especially when they also have a high interest in investing. Despite differences in the social and educational backgrounds of students at both universities, the roles of investment knowledge and interest as driving factors for investment decisions remain significant. This research offers practical implications for educational institutions and financial organizations to enhance financial literacy through programs that not only deliver information about investments but also motivate students to become more engaged in the world of investing. These findings emphasize the importance of combining knowledge and interest as the foundation for rational and active investment decision-making.